ADHD Symptoms, Entrepreneurial Orientation (EO), and Firm Performance. (January 2021) - Yu, Wei; Wiklund, Johan; Pérez-Luño, Ana
Recently, scholars have started to investigate the relationship between ADHD (Attention Deficit Hyperactivity Disorder) symptoms and entrepreneurship, finding that ADHD symptoms positively impact entrepreneurial intention and action. However, the performance implications of ADHD symptoms are still unknown. Using two samples of entrepreneurs from the United States and Spain, we find evidence that impulsive and hyperactive symptoms of ADHD are largely conducive to firm performance through entrepreneurial orientation (EO) while inattention symptoms are not. This suggests that the performance advantages of entrepreneurs ADHD symptoms can be derived from greater focus on innovation, proactiveness, and risk-taking. We discuss the implications of our findings for the entrepreneurship literature.